The Overlapping Consensus in the Indonesian Constitution and Its Challenges: Konsensus Berkeadilan dalam Konstitusi Indonesia dan Tantangan-tantangannya - Sunaryo, Sunaryo (Jurnal Konstitusi, 2023)
Pancasila and UUD 1945 form the foundation of Indonesia's social unity. This article analyzes whether Pancasila and UUD 1945 align with John Rawls' criteria of overlapping consensus. The article concludes that the agreement among Indonesia's founding fathers fulfills the requirements of an "overlapping consensus." This consensus encompasses principles of justice that remain independent of any comprehensive doctrine, ensuring the protection of citizens' fundamental rights and the most disadvantaged groups. Despite its imperfections, this consensus significantly contributes to Indonesian social unity. Nevertheless, the reality is marked by challenges and threats that require resolution. Some groups seek to dominate others, and specific rules deviate from the principles of justice. The state and society's commitment to uphold the overlapping consensus is crucial. Among the institutions entrusted with maintaining this consensus is the Constitutional Court.